City of fallen angels - Clare, Cassandra (New York Margaret K. McElderry Books, 2012)
As mysterious murders threaten the new peace between Shadowhunters and Downworlders, only Simon, the Daylighter vampire, can help bring both groups together
Includes bonus story, "When midnight comes."
Ages 14 up
1 14
NEW, LITERATURE
Keywords: Demonology -- Juvenile fiction; Demonology; Magic -- Juvenile fiction; Magic; Vampires -- Juvenile fiction; Vampires; New York (N.Y.) -- Juvenile fiction; New York (State) -- New York; Fiction; Juvenile works; Occult fiction